Use of osmoregulatory ability to predict invasiveness of the Indo-Pacific swimming crab Charybdis hellerii (A. Milne-Edwards, 1867) an invader in Southern Brazil - Occhi, Thiago Vinícius Trento; Vitule, Jean Ricardo Simões; Metri, Cassiana Baptista; Prodocimo, Viviane (Nauplius, 2019)
The Indo-Pacific swimming crab Charybdis hellerii (A. Milne-Edwards, 1867) is native to the Indo-Pacific Ocean, and occurs as an invasive species along the Eastern American coast, where it was probably introduced in ballast water. The present study evaluated the osmoregulation and salinity tolerance of C. hellerii in Paranagua Bay, Parana, Brazil, an estuary under the constant threat of introduction of non-native species. The crabs were abruptly submitted to salinities of 10, 20, 30 (control), and 40 PSU for 24h. Hemolymph osmolality showed either an increase or a decrease following the changes in water salinity, presenting a pattern of hyper-osmoconformation. Muscle water content was stable at salinities from 20 to 40 PSU, and increased after exposure to 10 PSU indicating cellular swelling. At 10 PSU a physiological limit was reached, indicated by the failure of the capacity to regulate tissue water content. Although adult C. hellerii tolerate a wide range of salinities for 24 h, its osmoregulatory ability indicates a possible advantage for its establishment in estuarine waters with salinities <20 PSU. The salinity tolerance and osmoregulatory data are important basic information to be used in models to predict and prevent the invasion of the species into new areas of the Neotropics